Effect of waste polyethylene terephthalate (PET) on properties of road aggregate - A. F., Ahmad; A. R., Razali; Intan Suhana, Mohd Razelan; W. A. H. W., Hamizan (IOP Publishing, 2019)
Rapid growth of plastics industries in Asia's emerging markets particularly in Malaysia, in one way, it raised expectations for everyday comforts, in the other way it also causes environmental issues. Plastic bottle for recycling can be found from the household waste stream, and most of them are made from Polyethylene Terephthalate (PET).Recycling this plastic into another form might be one of the cheapest and rapid solutions. However, turning this plastic into some other usable form uses energy and this may not become a green waste management solution. In this research, PET is utilized to explore its potential prospects to upgrade asphalt mixture properties. This study investigates the use of waste plastic as modifier for aggregates (plastic coating aggregate). The type of plastic used in this study was waste PET plastic bottle. The shredded waste PET plastic (size 0.075mm to 1.18mm) was mixed with hot aggregate to form a thin layer on the surface of the aggregates. The properties of modified aggregate and unmodified aggregate was tested and compared. 1% and 2% of plastic by weight of aggregate were used to coat the aggregate. The plastic-coated aggregates are tested for impact value and crushing value. The test results had demonstrated that there was an improvement in the properties of plastic coated aggregates.